Re-examining risk factors of genocide. Issue 1 (2nd January 2017) - Nyseth Brehm, Hollie
ABSTRACT: This article assesses the risk factors of genocide. Drawing upon previous research on genocide and the United Nations' Atrocity Prevention Framework, it employs an event history analysis of over 150 countries between 1955 and 2005. While existing frameworks emphasize general upheaval, this article disaggregates the type of upheaval, finding that economic upheaval—such as resource scarcity or population pressure—does not influence the odds of genocide. Instead, political upheaval that enables a repressive leader to come to power (including coups, assassinations, civil wars and successful revolutions) and political upheaval that directly threatens those in power (including coup attempts, campaigns against the state, unsuccessful revolutions and civil wars that do not coincide with regime change) have the strongest influence on the onset of genocide. These findings are consistent with previous findings that emphasize political upheaval and threat but specify numerous indicators of these broad phenomena. This article also highlights the role of discrimination and exclusion, although it casts doubt on many other risk factors included in recent case studies and in the United Nations' Atrocity Prevention Framework.